User statistics of the UP Diliman General Reference and Electronic Resources Section, University Library a multivariate trend analysis, 2005-2011 - Senga, Karlo Gabriel A.; Lapuz, Elvira B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2013)
The study looked at the annual reports of the General Reference Library in order to find trends and patterns within the data, and to explain, using internal library factors, why they came to be. The available annual reports from 2005-2011 were used, and based on the completeness of data, the records used were divided into collections, staffing, expenditures, and service activities, which corresponds to the ARL Statistics coverage. Numerous errors and inconsistencies were found in the reports, and were cross-referenced for verification.
The study found a significant decrease in readers admitted for the library in recent years. After experiencing a steady growth of users during the preceding years, peaking at almost 200,000 readers, the number dropped by as much as 54% in 2010, and continued to decline in 2011. The 2010 report made no mention of this decrease due to an erroneous records, and the 2011 record, and the 2011 report attributed it to the electrical problems experienced by the library from October 2010 to February 2011, where sections of the Main Library received limited to no power supply.
Looking at the monthly user patterns of the library, however, the study concluded that the power problems could not have played a significant role in the decrease, as the months affected had relatively fewer users in general. During 2010, the study estimated that the power problems exacerbated the decrease by a mere 6%.
Library expenditures were not insufficient, quadrupling in amount within the 6-year period. Collection growth was slowly decreasing, but a study on ARL libraries have found that serial costs are rising rapidly compared to all other expenditures, and as such, take up a larger amount of the budget, while monograph acquisitions are declining to compensate.
The study found that on 2009, the year immediately preceding the significant decrease in users, there were three noticeable records. First is that the number of readers admitted peaked during that year, at 197,122. Second is that the number of staff employed by the library was at an all-time low, at only 8.5 FTE, excluding student assistants. Lastly, user orientation and tours were also at a record low that year. The study concluded that the combination of these factors led to 1) an impression that the library was understaffed and was not able to fully service all of its clients and 2) fewer users being introduced to the library and educated in how to use it, both of which led to a decline in users the following year.
The study recommends the following things: that the library prepare its records more carefully, that it strive to keep its staffing sufficient and to prepare for the busiest months accordingly, that it encourage as many orientations and tours as possible, and that it advertise its new acquisitions and upgrades more prominently, instead of being limited to new monographs.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philipines (Diliman) Main Library General Reference Section; Library statistics -- Philippines -- Quezon City